Female parental consanguinity is associated with a reduced ovarian reserve. Issue 4 (April 2022) - Melado, Laura; Lawrenz, Barbara; Loja, Raquel; Coughlan, Carol; Altobelli, Gioia; Bayram, Asina; Arnanz, Ana; Elkhatib, Ibrahim; De Munck, Neelke; Fatemi, Human
Abstract: Research question: Is parental consanguinity associated with a reduced ovarian reserve in women from the Arabian Peninsula, comparing anti-Müllerian hormone (AMH) and antral follicle count (AFC)? Design: Retrospective large-scale observational study including 2482 women from the Arabian Peninsula, aged 19–49 years, who had their serum AMH and AFC measured as part of their fertility assessment, from May 2015 to November 2019. Consanguinity was defined as women whose parents were first-degree or second-degree cousins. Serum AMH was measured for all participants. Results: A total of 2198 women were included: 605 in the consanguine group (27.53%), 1593 (72.47%) in the non-consanguine group. There were no significant differences between groups in terms of body mass index, years of infertility or smoking status. Women from the consanguine group were significantly younger (mean age 33.74 ± 6.64 years) compared with the non-consanguine group (mean age 34.78 ± 6.64 years, P < 0.0001). Median AMH and AFC for the consanguine group were 1.90 ng/ml (min–max: 0.01–23.8) and 11 (0–80), respectively, and for the non-consanguine group 1.84 ng/ml (min–max: 0.01–23.0) and 11 (0–60), respectively. AMH and AFC exhibit an age-dependent decline. As both parameters are age-dependent, the multivariate analysis showed that women from the consanguine group presented significantly lower AMH (coefficient of variation [CV] –0.07 ± 0.03, P = 0.036) and AFC (CV –0.16 ± 0.06, P = 0.003) compared with non-consanguine women, and the highest differences were found for women below 35 years of age (AMH median [min–max]: 2.82 ng/ml (0.01–23.80) versus 2.92 ng/ml (0.01–23.00); P = 0.035; AFC median [min–max]: 15 (0–80) versus 14 (0–80); P = 0.001). Conclusion: The adjusted analysis by age indicates that female parental consanguinity is associated with reduced ovarian reserve in the studied population. Clinical evaluation should include extensive family history and subsequent counselling of the affected couples.